Disturbance in hemoglobin metabolism and in vivo antimalarial activity of azole antimycotics - Rodrigues, Juan Ricardo; Lourenco, Diana; Gamboa, Neira (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
Plasmodium parasites degrade host hemoglobin to obtain free amino acids, essential for protein synthesis. During this event, free toxic heme moieties crystallize spontaneously to produce a non-toxic pigment called hemozoin or ß-hematin. In this context, a group of azole antimycotics, clotrimazole (CTZ), ketoconazole (KTZ) and fluconazole (FCZ), were investigated for their abilities to inhibit ß-hematin synthesis (IßHS) and hemoglobin proteolysis (IHbP) in vitro. The ß-hematin synthesis was recorded by spectrophotometry at 405 nm and the hemoglobin proteolysis was determined by SDS-PAGE 12.5%, followed by densitometric analysis. Compounds were also assayed in vivo in a malaria murine model. CTZ and KTZ exhibited the maximal effects inhibiting both biochemical events, showing inhibition of β-hematin synthesis (IC50 values of 12.4 ± 0.9 µM and 14.4 ± 1.4 µM respectively) and inhibition of hemoglobin proteolysis (80.1 ± 2.0% and 55.3 ± 3.6%, respectively). There is a broad correlation to the in vivo results, especially CTZ, which reduced the parasitemia (%P) of infected-mice at 4th day post-infection significantly compared to non-treated controls (12.4 ± 3.0% compared to 26.6 ± 3.7%, p = 0.014) and prolonged the survival days post-infection. The results indicated that the inhibition of the hemoglobin metabolism by the azole antimycotics could be responsible for their antimalarial effect.